2017
DOI: 10.1038/nature23658
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal LTP and contextual learning require surface diffusion of AMPA receptors

Abstract: Long-term potentiation (LTP) of excitatory synaptic transmission has long been considered a cellular correlate for learning and memory1,2. Early LTP (eLTP, <1 hour) had initially been explained either by presynaptic increases in glutamate release3–5 or by direct modification of post-synaptic α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) function6,7. Compelling models have more recently proposed that synaptic potentiation can occur by the recruitment of additional post-synaptic AMPARs8, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
302
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(346 citation statements)
references
References 33 publications
28
302
0
Order By: Relevance
“…Using this approach, we detected reliable NMDA receptor-dependent GluA1 surface delivery following cLTP (Figures 2E and 2F; no cLTP 100.0% ± 3.2%, cLTP 118.2% ± 3.2% [p = 0.011 versus no stimulation], and cLTP + D-2-amino-5-posphonovalerate (AP5) 99.4% ± 3.4% [p = 0.0006 versus cLTP]). While this increase is modest, we note that the size of the effect that we identified is consistent with the degree of synaptic potentiation that requires postsynaptic insertion of GluA1-containing AMPA receptors (Penn et al, 2017). Consistent with our previous results demonstrating a critical role for L-VGCCs in regulating RE cargo delivery to the PM, we found that pharmacologically blocking L-VGCCs with either nimodipine (10 μM) or verapamil (25 μM) also prevented activity-triggered membrane insertion of GluA1-containing AMPA receptors (Figures 2E and 2F; cLTP 118.2 ± 3.2%, cLTP + nimodipine [Nim] 99.24 ± 1.6 [p = 0.0003 versus cLTP], and cLTP + verapamil [Verap] 95.8 ± 2.2 [p < 0.0001 versus cLTP]).…”
Section: Resultssupporting
confidence: 79%
“…Using this approach, we detected reliable NMDA receptor-dependent GluA1 surface delivery following cLTP (Figures 2E and 2F; no cLTP 100.0% ± 3.2%, cLTP 118.2% ± 3.2% [p = 0.011 versus no stimulation], and cLTP + D-2-amino-5-posphonovalerate (AP5) 99.4% ± 3.4% [p = 0.0006 versus cLTP]). While this increase is modest, we note that the size of the effect that we identified is consistent with the degree of synaptic potentiation that requires postsynaptic insertion of GluA1-containing AMPA receptors (Penn et al, 2017). Consistent with our previous results demonstrating a critical role for L-VGCCs in regulating RE cargo delivery to the PM, we found that pharmacologically blocking L-VGCCs with either nimodipine (10 μM) or verapamil (25 μM) also prevented activity-triggered membrane insertion of GluA1-containing AMPA receptors (Figures 2E and 2F; cLTP 118.2 ± 3.2%, cLTP + nimodipine [Nim] 99.24 ± 1.6 [p = 0.0003 versus cLTP], and cLTP + verapamil [Verap] 95.8 ± 2.2 [p < 0.0001 versus cLTP]).…”
Section: Resultssupporting
confidence: 79%
“…Banker cultures of hippocampal neurons from E18 Sprague-Dawley rat embryos of either sex were prepared as described previously (Penn et al, 2017). Neurons (10–12 days in vitro [DIV]) were transfected using Effectene as per the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Western blots and cLTP experiments were prepared as described previously (Penn et al, 2017). Cultured hippocampal neurons at DIV 14 were treated either with vehicle or 1 μM oAβ diluted in Tyrode’s buffer during 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Submillimolar to millimolar concentrations of glutamate are reached within the synaptic cleft upon vesicular release, and therefore, AMPARs are usually placed in direct opposition to the active zone where they mediate synaptic signaling. AMPARs can also be found extrasynaptically, but those are required for efficient trafficking in and out of the synapse underlying rapid changes in the synaptic strength (Penn et al, ; Wu et al, ). NMDARs, KARs, and mGluRs may be placed extrasynaptically on postsynaptic neurons, and/or on glial cells; mGluRs are also often found on the presynaptic terminals where they regulate neurotransmitter release.…”
Section: Glutamatergic Synaptic and Extrasynaptic Signaling Between Nmentioning
confidence: 99%